+0  
 
+1
99
5
avatar+27 

 Pls help, Im confused :( A clear solution would help. (Also, to whoever was pretending to be me when I was a guest and making people think I was a spammer, please don't do that to other guests, its not nice) Thanks!

 Nov 19, 2020
 #1
avatar
+1

(a) f(x) = (x - 1)/(x - 3)

 

(b) f(x) = (x - 1)/(2x - 6).

 Nov 19, 2020
 #2
avatar+27 
+1

Thank you so much! Im still a little confused how you got that though, could you give me an explanation?

 Nov 19, 2020
 #3
avatar+153 
+1

Imagine if that was the same one who acted like they were youangry

Thanks4helping  Nov 19, 2020
 #4
avatar+116125 
+2

1st one

 

The horizontal asymptote   will be given  by the ratio  of the  coefficients on the variable x in the numerator and denominator

 

So      a/1  = -4      implies that  a  = -4

 

A vertical asymptote  will occur when the  denominator   = 0 

 

So....when x=  3 we have that     3 + c  = 0    →   c = -3

 

And since  f(1)  = 0.....this means that

 

0  = -4(1) +  b

     _________     multiply  both sides  by   x -3

         x - 3   

 

So we have

 

0  = -4 + b     →   b =  4

 

Our  function is

 

f(x)   =   -4x  + 4

             _______

               x - 3

 

Here is the graph  :

https://www.desmos.com/calculator/vgpwl6hezj

 

cool cool cool       

 Nov 19, 2020
 #5
avatar+116125 
+2

Second one .....this one is a little tougher

 

Similar to the  first....we have  that

r/2  =  -4        multiply both sides by 2

r  =  -8

 

Since we have a vertical asymptote at x = 3....we need to solve this

2(3) + t  =0

6 + t = 0

t  = -6

 

And since  the point (1,0)  is on the graph, we can ignotr the denomiantor and solve

-8(1)   +  s  = 0

-8 + s  = 0

s= 8

 

Our function is

 

f(x)  =  -8x  + 8

          _______

             2x  -6 

 

Graph here  :   https://www.desmos.com/calculator/plavxacf5r

 

cool cool cool

 Nov 19, 2020

24 Online Users

avatar